THE ROLE OF SELF-EFFICACY IN PHYSICAL ACTIVITY IN STUDENTS: A LITERATURE REVIEW - Reide, Lasma; Veseta, Una; Ābele, Agita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Physical activity among adults and adolescents do not meet the recommendations of WHO. Many studies focus on investigation of physical activity in students and the role of self-efficacy as important factor in predicting physical activity behaviour. Aim of the study was to determine the role of self-efficacy in physical activity in students. A literature review has been conducted to determine the self-efficacy measurements in physical activity studies and to determine factors related to self-efficacy and physical activity. Through search in the PubMed database 206 records were identified and 24 articles were included in further analysis. Thirteen studies used the General Self-Efficacy Scale [GSES] to measure self-efficacy level. Two studies considered The Exercise Self-Efficacy scale [ESES] focusing specifically on physical activity. Other studies considered different self-efficacy measurement tools including separate questions about physical activity self-efficacy as part of the questionnaire or survey used in the study. One study focused on emotional self-efficacy measures. Other factors investigated in relation to self-efficacy and physical activity were health beliefs, anxiety, depression, perceived stress, academic behaviour, academic procrastination, academic burnout, emotional intelligence, subjective well-being, Self-control, motivation and addiction, self-esteem, body image, sense of inferiority, and social support.